PENGARUH PENDAPATAN TERHADAP KONSUMSI DAGING BABI DI KECAMATAN WANEA KELURAHAN RANOTANA WERU - Keintjem, Ridel .; Oley, F. S.; Lensun, G. D.; Pandey, J (ZOOTEC, 2016)
ABSTRACT INCOME EFFECT ON CONSUMPTION OF PORK IN WANEA DISTRCT RANOTANA WERU VILLAGE This study aims to determine the effect of family income to the consumption of pork and substitutes, in Wanea district, Ranotana Weru village. The survey method used to obtain secondary data and primary data. Samples were obtained by purposive sampling, and to get answers from the purpose of this study, the formula of multiple regression analysis is used: C = b0 + b1 x1 + b2 x2 + b3 x3, and obtained the analysis of the influence of family income on the consumption of pork in Ranotana Weru village as the following: C = 59.44 + 1.38 (x1) + 0,018 (x2) + 4.97 (x3) R2 = 0.95. From the results of the equation, the value of the intercept of 59.44 indicates that no change in the price of pork, the price of substitutes and without changes in income, then the people in Ranotana Weru village keep eating pork amounted to 59.44 grams (per person?). See the regression coefficient value of the price of pork of 1.38, meaning in any increase in the price of pork Rp 1.000, the consumption of pork decreased by 1.38 grams (per person?), Â Seethe price regression coefficient value of substitutes0.018, means any increase in the price of substitutes Rp 1.000, the substitution of consumption goods rose by 0,018 grams. See the earnings darai regression coefficient 4.97, meaning any increase in revenue to Rp 1.000, the consumption of pork will rise by 4.97 grams and R2 value of 0.95 indicates that variations in rise and fall of the consumption of pork and substitutes at 95 % influenced by factors family income and sisnya 5% influenced by other factors not included in the model equations. Family income significantly affect the consumption of pork and substitutes in the village ranotana Weru. This is evidenced by the results of the t test of 0.786 is smaller than Ttabel 2,000. Â  Keywords: Income, consumption of pork, substitutes